Mimetic Dominance and the Economics of Exclusion: Private Goods in Public Context - Alex Imas; Kristóf Madarász (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We propose a simple mechanism of mimetic dominance whereby a person's valuation for consuming an object or possessing an attribute is increasing in others' unmet desire for it. Such mimetic preferences help explain a host of market anomalies and generate novel predictions in a variety of domains. In bilateral exchange, people exhibit a social endowment effect, and there is an increased demand for goods that become relatively more scarce. A classic monopolist earns excess profit by randomly excluding some people from being able to purchase the product. We test the predictions of the model empirically across several exchange environments. When auctioning a private good, we find that randomly excluding people from the opportunity to bid substantially increases average bids amongst those who retain this option. Furthermore, exclusion leads to greater expected revenue than increasing competition through inclusion. This effect is absent when bidders know that those who are excluded have lower desires for the good. We demonstrate that mimetic preferences matter even for basic exchange: a person's demand for a good increases substantially when others are explicitly excluded from the opportunity to buy the same kind of good. Mimetic preferences have implications for both price and non-price based methods of exclusion: the model predicts Veblen effects, rationalizes attitudes against redistribution and trade, and provides a novel motive for social stratification and discrimination.
Keywords: 330; mimetic preferences; objects of desire; exclusion; trade; competition; inequality